Low medical morbidity and mortality after acute courses of electroconvulsive therapy in a population‐based sample. (18th September 2017) - Blumberger, D. M.; Seitz, D. P.; Herrmann, N.; Kirkham, J. G.; Ng, R.; Reimer, C.; Kurdyak, P.; Gruneir, A.; Rapoport, M. J.; Daskalakis, Z. J.; Mulsant, B. H.; Vigod, S. N.
Abstract : Background: To determine event rates for specific medical events and mortality among individuals receiving electroconvulsive therapy (ECT). Method: Population‐based cohort study using health administrative data of acute ECT treatments delivered in Ontario, Canada, from 2003 to 2011. We measured the following medical event rates, per 10 000 ECT treatments, up to 7 and 30 days post‐treatment: stroke, seizure, acute myocardial infarction, arrhythmia, pneumonia, pulmonary embolus, deep vein thrombosis, gastrointestinal bleeding, falls, hip fracture, and mortality. Results: A total of 135 831 ECT treatments were delivered to 8810 unique patients. Overall medical event rates were 9.1 and 16.8 per 10 000 ECT treatments respectively. The most common medical events were falls (2.7 and 5.5 per 10 000 ECT treatments) and pneumonia (1.8 and 3.8 per 10 000 ECT treatments). Fewer than six deaths occurred on the day of an ECT treatment. This corresponded to a mortality rate of less than 0.4 per 10 000 treatments. Deaths within 7 and 30 days of an ECT treatment, excluding deaths due to external causes (e.g., accidental and intentional causes of death), were 1.0 and 2.4 per 10 000 ECT treatments respectively. Conclusion: Morbidity and mortality events after ECT treatments were relatively low, supporting ECT as a low‐risk medical procedure.